2018
DOI: 10.1021/acsanm.8b01748
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineered High-Performance Hexaferrite Magnets by Morphology-Induced Alignment of Tailored Nanoplatelets

Abstract: Magnetic materials are ubiquitous in electric devices and motors making them indispensable for modern-day society. The hexaferrites currently constitute the most widely used permanent magnets (PMs), accounting for 85% (by weight) of the global sales of PMs. This work presents a complete bottom-up nanostructuring protocol for preparation of magnetically aligned, high-performance hexaferrite PMs with a record-high (BH)max for dry-processed ferrites. The procedure includes the supercritical hydrothermal flow synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 64 publications
1
55
1
Order By: Relevance
“…In turn, the specimens prepared at 1000 ºC (red and blue colors) show the lowest HC (<5800 Oe), while all the samples synthesized in the range 800 -900 ºC (black, orange and green colors in Figure 2a-b) display a HC 6000 Oe. This is likely explained by the fact that higher temperatures lead to an increase in particle size which is known to reduce the HC in the multidomain magnetic region [25][26][27][28]. In particular, the sequence 300 -900 ºC yields to HC ~6350 Oe, which is one of the highest value reported for SFO nanocrystalline powders synthesized by a citrate combustion [14].…”
Section: Optimization Of the Thermal Treatmentmentioning
confidence: 97%
“…In turn, the specimens prepared at 1000 ºC (red and blue colors) show the lowest HC (<5800 Oe), while all the samples synthesized in the range 800 -900 ºC (black, orange and green colors in Figure 2a-b) display a HC 6000 Oe. This is likely explained by the fact that higher temperatures lead to an increase in particle size which is known to reduce the HC in the multidomain magnetic region [25][26][27][28]. In particular, the sequence 300 -900 ºC yields to HC ~6350 Oe, which is one of the highest value reported for SFO nanocrystalline powders synthesized by a citrate combustion [14].…”
Section: Optimization Of the Thermal Treatmentmentioning
confidence: 97%
“…In a recent study by Saura-Múzquiz et al it was demonstrated, how the initial size and shape of the nanocrystalline powder was hugely affecting the texture. 40 Neutron powder diffraction was also used to infer information about the magnetic structure at the atomic scale. Magnetic interactions between the crystallites, as well as the role of grain boundaries on the evolution of H c and M r is complicated 41 and have not been addressed in this work.…”
Section: Inuence Of Uniaxial Pressurementioning
confidence: 99%
“…Still, important properties such as the electronic gap have not yet been determined. In the last 2 decades, significant effort has been devoted to improve its magnetic performance, particularly for permanent magnet applications, by chemical substitution and nanostructuring [3][4][5][6][7] . Nanometric thin SFO platelets have been recently characterized combining fundamental experimental techniques, as X-ray absortion based and Mössbauer spectroscopies, to density functional theory (DFT) calculations intended to rationalize Oxygen K absortion edge spectrum measurements 8 .…”
mentioning
confidence: 99%